(untitled) (REMUNOM, 2025)
The Supervised Curricular Internship represents an excellent opportunity for students to experience real-world situations, deepen their knowledge and skills in their area of interest, and gain a better understanding of the professional work environment. The objective of this report was to describe the experiences of an undergraduate student in the Agronomy program during the Supervised Curricular Internship. The internship was carried out from July 21 to October 2, 2025, in the experimental area of the Federal University of Fronteira Sul – Chapecó Campus, totaling 306 hours. The area comprises 16 hectares, including orchards, vegetable and annual crop plots, greenhouses, a weather station, and other facilities dedicated to academic, research, and extension activities. Overall, the internship provided a comprehensive practical experience, enabling direct involvement in teaching, research, and extension activities across different fields of agricultural sciences. Over the eleven-week period, the student engaged in a wide range of tasks that fostered the development of essential technical and operational competencies for professional training. Additionally, the experience strengthened organizational and management skills, allowing a better understanding of the integration between teaching, research, and extension. The immersion in a dynamic and multifunctional environment highlighted the importance of adaptability, critical observation, and evidence-based decision-making—skills that are indispensable for future agronomists—and contributed significantly to both academic and professional development.